An advanced and efficient asymmetric PCR method for microarray applications - Reddy Banda, Suresh; Klapproth, Holger; Smit, Nicolaas; Bednar, Sonja; Brandstetter, Thomas; Rühe, Jürgen (Frontiers in Bioengineering and Biotechnology, 2022)
The sensitivity of a PCR based biochip assay relies on the efficiency of PCR amplicons in binding to the microarray spots. The essential factor is the amount of single stranded (ss) amplicons available for biochip hybridization. Asymmetric PCR can generate ss-amplicons depending on the ratio of primers used but this is often inefficient. We report a novel variant of PCR called the Asymmetric Exponential and Linear Amplification (AELA) which can overcome these issues and generate large amounts of single stranded amplicons. AELA-PCR introduces an amplification strategy that encourages both exponential and linear amplification of the target nucleic acid. This is done by specifically designed primers and choice of a thermal profile such that both primers can amplify in the exponential phase whereas only one primer can amplify in the linear phase. This results in generation of a large pool of amplified target in the exponential phase which are then used as a template to produce to ss-amplicons in the linear phase. These adaptions in PCR are particularly idle where the generation of ss-DNA/RNA is required. We demonstrate the higher biochip sensitivity of AELA-PCR compared to conventional amplification methods with an example of the Staphylococcus aureus detection on a DNA oligonucleotide microarray.